(untitled) - Usunier, Jean-Claude (London, 2017)
Successfully combining cross-cultural management and business research methods, this team of international authors provide much needed coverage of the implications that should be considered when undertaking research across different cultures
Keywords: Kinh doanh,Business; Nghiên cứu đa văn hóa,Cross-cultural studies